THE RELATIONSHIP BETWEEN SELF-ACCEPTANCE AND THE NARCISSISTIC TENDENCIES OF STUDENTS USING INSTAGRAM SOCIAL MEDIA - Dhea Puspa Dewi; Widyastuti (P3I UMSurabaya, 2024)
This study aims to determine the relationship between self-acceptance and narcissistic tendencies in students who use Instagram social media in Sidoarjo. The hypothesis proposed is that researchers argue that there is a relationship between self-acceptance and narcissistic tendencies. The method used is quantitative with a correlational approach. The population in this study was 23,039 and the sample was 85 using G-Power with random sampling technique. The result is a significant relationship that obtained a value (rxy) of 0.285. Hypothesis testing shows a significance value of 0.008, so the hypothesis can be accepted, and R Square is 8.1%. So it can be concluded that self-acceptance is weak against narcissistic tendencies, for that further researchers are expected to add other variables that have coverage of narcissistic tendencies.